Metal lithium composite negative electrode, preparation method thereof and metal lithium battery
By using carbon fluorinated materials, nanocarbon materials and interface stabilizers in the interface stabilization layer of metal lithium composite negative electrode, the problems of easy cracking of the protective layer and poor structural stability during the circulation process of metal lithium negative electrode are solved, and excellent circulation performance and rate performance are achieved.
Patent Information
- Application Number
- CN202510185433.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
AI Technical Summary
During the circulation process, the existing metal lithium negative electrode has problems such as the protective layer is prone to rupture and poor structural stability, which affects its circulation performance and rate performance.
A metal lithium composite negative electrode is designed, which contains an interface stabilization layer. The interface stabilization layer is composed of micro-nano-scale carbon fluoride material, nano-carbon material and interface stabilizer. The fluoride material contacts the lithium-containing layer and generates lithium fluoride in situ. The nano-carbon material regulates the uniform distribution of electrons and lithium ions in the interface layer, and the interface stabilizer enhances the structural stability of the interface stability layer.
It has achieved a metal lithium composite negative electrode with good interface stability, with excellent cycle performance and rate performance, and overcomes the problems of easy cracking of the protective layer and poor structural stability.
Smart Images

Figure CN119673966A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a metal lithium composite negative electrode and a preparation method thereof, and a metal lithium battery. Background Art
[0002] Metal lithium has high specific capacity (3860mAh / g) and low density (0.534g / cm 3 ) and good ductility, and has been widely studied. However, during the cycle, lithium metal has problems such as volume expansion, lithium dendrites and dead lithium. In particular, the continuous growth of lithium dendrites may further cause safety problems (such as fire, explosion, etc.). These factors have greatly limited the commercial application of lithium metal anodes.
[0003] At present, surface modification is one of the main research aspects of lithium metal negative electrode. Among them, surface modification on the surface of lithium metal can improve the interfacial stability between the lithium metal negative electrode and the electrolyte and solve the problem of lithium dendrites. CN108448058B discloses a lithium metal negative electrode with a surface rich in lithium fluoride. The preparation method of the negative electrode comprises: in a dry protective gas atmosphere, immersing the lithium metal negative electrode in a fluorine-containing ionic liquid, or applying the fluorine-containing ionic liquid on the surface of the lithium metal negative electrode, after fluorination, taking it out, forming a protective layer rich in lithium fluoride on the surface of the lithium metal negative electrode, and obtaining a lithium fluoride-coated lithium metal negative electrode. However, as the cycle proceeds, the lithium fluoride protective layer on the surface of the lithium metal negative electrode is prone to rupture, and the interface stability is poor, which in turn affects the cycle performance.
[0004] CN110957492A discloses a lithium metal interface protection, which is mainly composed of a fluorinated carbon material, a matrix material and a functional additive material. The lithium metal interface protection has no stable components, the structure is unstable, and each component is easy to fall off, which deteriorates the performance of the negative electrode.
[0005] Based on this, how to design a metal lithium composite negative electrode with a stable protective layer structure and good interface stability to overcome the above-mentioned shortcomings such as easy rupture of the protective layer and poor structural stability during charging and discharging has become an urgent problem to be solved at this stage. Summary of the invention
[0006] In view of the problems existing in the prior art, the present application provides a metal lithium composite negative electrode, a preparation method thereof, and a metal lithium battery. The composite negative electrode is provided with an interface stabilization layer on the surface of the lithium-containing layer. The structure of the interface stabilization layer is stable, and the uniform deposition of metal lithium can be regulated to inhibit the generation and growth of lithium dendrites. The composite negative electrode has good interface stability and excellent cycle performance and rate performance.
[0007] To achieve this goal, this application adopts the following technical solutions:
[0008] In a first aspect, the present application provides a metal lithium composite negative electrode, the negative electrode comprising a lithium-containing layer, an interface stabilization layer being arranged on the surface of the lithium-containing layer; the interface stabilization layer comprising micro-nano-scale carbon fluoride materials, nanocarbon materials and an interface stabilizer, the carbon fluoride material generates lithium fluoride in situ at the contact position with the lithium-containing layer; at least one of the carbon fluoride material and the nanocarbon material is a linear, tubular or sheet-like material, and the interface stabilizer comprises a styrene structural unit.
[0009] In the present application, the carbon fluoride material, nanocarbon material and interface stabilizer are basically evenly distributed in the interface stabilization layer, wherein in the part of the interface stabilization layer in contact with the lithium-containing layer, the carbon fluoride material reacts with metallic lithium to generate lithium fluoride and carbon, lithium fluoride is one of the components of the solid electrolyte interface (SEI) film, plays a role in stabilizing the interface, and carbon plays a role in retaining liquid and regulating the uniform distribution of electrons; the carbon fluoride material in the interface stabilization layer that is not in contact with the lithium-containing layer is less conductive than metallic lithium, and can regulate the transmission and deposition of lithium ions to the lithium-containing layer, and inhibit the growth of lithium dendrites on the surface of the composite negative electrode. The nanocarbon material regulates the uniform distribution of electrons and lithium ions in the interface layer, promotes the performance of the carbon fluoride material, and improves the rate performance of the composite negative electrode. At least one of the carbon fluoride material and the nanocarbon material is a linear, tubular or sheet-like material, which can connect the components in the interface stabilization layer, and the interface stabilizer can enhance the structural stability of the interface stabilization layer, and at the same time can enhance the mechanical properties of the surface of the lithium-containing layer, slow down the pulverization of the lithium-containing layer, and improve the cycle performance of the composite negative electrode.
[0010] In the present application, the specific selection of the interface stabilizer utilizes the hard and strong characteristics of the styrene structural unit, and can enhance the mechanical properties of the interface stabilization layer while connecting the components, improve the stability of the composite negative electrode, and is not easy to fall off during the cycle. The components in the interface stabilization layer cooperate with each other and work synergistically, have a stable structure, and regulate the uniform deposition of metallic lithium at the same time. The metallic lithium composite negative electrode has a stable contact interface with the electrolyte, can achieve high rate charge and discharge, and has excellent rate performance and cycle performance.
[0011] Optionally, the lithium-containing layer includes metallic lithium and / or a lithium alloy, the alloying elements in the lithium alloy include at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum or zinc, and the content of metallic lithium in the lithium alloy is more than 50%, preferably more than 80%, and more preferably more than 90%.
[0012] Optionally, the thickness of the lithium-containing layer is 1-100 μm, preferably 5-50 μm.
[0013] Optionally, the fluorinated carbon material includes at least one of fluorinated graphite, fluorinated activated carbon, fluorinated carbon black, fluorinated graphene or fluorinated graphene oxide;
[0014] Optionally, the atomic ratio of carbon to fluorine in the fluorinated carbon material is greater than 0 and less than 1.25, for example, it can be 0.1, 0.25, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2 or 1.25, including but not limited to the listed point values. The atomic ratio can take into account both the in-situ construction of a complete SEI and the regulation of electron transport, and is preferably 0.5-1.
[0015] Optionally, the size of the carbon fluoride material is 1nm-50μm, preferably a nanoscale carbon fluoride material, with a size of 3nm-500nm, more preferably 5-300nm. It should be noted that the nanoscale in the nanoscale carbon fluoride material only needs to satisfy the nanoscale size in at least one of the three-dimensional directions.
[0016] Optionally, the nano-carbon material includes at least one of carbon nanofibers, carbon nanotubes, graphene, acetylene black, Super P carbon black or Ketjen black.
[0017] Optionally, the number of layers of the carbon nanotubes is less than or equal to 15 layers, preferably 1-10 layers.
[0018] Optionally, the outer diameter of the carbon nanotube is less than 30 nm, preferably 1-20 nm.
[0019] Optionally, the length of the carbon nanotubes is 0.5 μm to 50 μm, preferably 1-30 μm.
[0020] Optionally, the interface stabilizer includes a copolymer of styrene and olefin, preferably at least one of styrene-butadiene rubber, polystyrene, styrene-ethylene-styrene block copolymer, styrene-butadiene-styrene triblock copolymer or styrene-ethylene-butylene-styrene block copolymer. The preferred interface stabilizer includes hard and strong styrene structural units and soft and elastic olefin units to form a network structure, so that the interface stabilization layer has elasticity and can adapt to the volume change of the lithium-containing layer during the cycle, further improving the cycle performance of the composite negative electrode.
[0021] Optionally, the mass ratio of the carbon fluoride material to the nanocarbon material in the interface stabilization layer is 1:(0.1-10). If the mass ratio is too small, there is too little carbon fluoride material, and the stabilizing effect of the interface stabilization layer is weak; if the mass ratio is too large, there is too little nanocarbon material, and the structural stability of the interface stabilization layer is poor and the interface resistance is high. Preferably, it is 1:(0.5-5).
[0022] Optionally, the mass ratio of the nano-carbon material to the interface stabilizer is 1:(0.1-10), preferably 1:(0.5-5).
[0023] Optionally, the mass ratio of the fluorinated carbon material, the nanocarbon material and the interface stabilizer in the interface stabilization layer is (0.1-10):1:(0.1-10). The interface stabilization layer has a stable structure and good interface contact, so that the performance of the composite negative electrode is excellent, preferably (0.5-5):1:(0.5-5).
[0024] Optionally, the thickness of the interface stabilization layer is 1-20 μm. If the thickness is too large, the transmission path of lithium ions will be increased, the interface resistance will be large, which is not conducive to high-rate charge and discharge. If the thickness is too small, it will not protect the lithium-containing layer. Preferably, it is 2-10 μm.
[0025] Optionally, the thickness ratio of the interface stabilizing layer to the lithium-containing layer is 1:(0.1-100), preferably 1:(1-50), and more preferably 1:(5-20). The thickness ratio is appropriate so that the composite negative electrode has both rate performance and cycle performance.
[0026] Preferably, the interface stabilizing layer is embedded in the lithium-containing layer, and the embedding depth is 0.1-5 μm. The interface stabilizing layer is embedded in the lithium-containing layer, which significantly improves the structural stability of the composite negative electrode.
[0027] Optionally, the composite negative electrode further includes a current collector, and the current collector includes at least one of copper foil, carbon-coated copper foil, textured copper foil, nickel foil, stainless steel foil, copper-tin composite foil or copper-nickel composite foil.
[0028] In a second aspect, the present application provides a method for preparing the composite negative electrode as described in the first aspect above, the method comprising the following steps:
[0029] (1) mixing a fluorinated carbon material, a nanocarbon material, an interface stabilizer and an organic solvent to obtain a mixture;
[0030] (2) The mixture in step (1) is placed on the surface of the lithium-containing layer to obtain the composite negative electrode.
[0031] Optionally, the organic solvent includes but is not limited to at least one of liquid alkanes with a carbon atom content of 5 to 20, benzene, p-xylene, solvent oil D40, solvent oil D60, solvent oil D80, N-methylpyrrolidone or N,N-dimethylformamide. As long as the fluorinated carbon material, nanocarbon material and interface stabilizer can be evenly dispersed and used as a solvent, it belongs to the protection scope of the present invention.
[0032] Optionally, the mixture in step (2) is disposed on the surface of the lithium-containing layer in a manner comprising at least one of coating, screen printing or transfer printing.
[0033] Optionally, step (2) further comprises the following operation: after the mixture is disposed on the surface of the lithium-containing layer, rolling is performed. Rolling can embed the interface stabilizing layer into the lithium-containing layer, making the composite negative electrode structure more stable.
[0034] In a third aspect, the present application provides a metal lithium battery, wherein the metal lithium battery comprises the composite negative electrode as described in the first aspect above.
[0035] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0036] (1) In the composite negative electrode provided by the present application, the fluorinated carbon material in the interface stabilization layer that is in contact with the lithium-containing layer can generate lithium fluoride in situ, thereby stabilizing the surface of the lithium-containing layer; the fluorinated carbon material that is not in contact with the lithium-containing layer has a weaker conductivity than metallic lithium, thereby regulating the transmission and deposition of lithium ions to the lithium-containing layer, thereby inhibiting the generation and growth of lithium dendrites in the composite negative electrode;
[0037] (2) In the composite negative electrode provided by the present application, the nanocarbon material in the interface stabilization layer homogenizes lithium ions and electrons and promotes the performance of the fluorinated carbon material; at least one of the fluorinated carbon material and the nanocarbon material is a linear, tubular or sheet-shaped material, which connects the components in the interface stabilization layer and cooperates with the interface stabilizer to significantly improve the structural stability of the interface stabilization layer. At the same time, it can enhance the mechanical properties of the surface of the lithium-containing layer, slow down the pulverization of the lithium-containing layer, and improve the cycle performance of the composite negative electrode;
[0038] (3) The specific selection of the interface stabilizer in the interface stabilization layer of the composite negative electrode provided in the present application makes the structure of the interface stabilization layer stable and have good mechanical properties, enhances the mechanical properties of the surface of the lithium-containing layer, slows down the pulverization of the lithium-containing layer, and significantly improves the cycle performance of the composite negative electrode;
[0039] (4) The composite negative electrode provided in the present application is designed with specific parameters such as the thickness ratio of the lithium-containing layer and the interface stabilization layer, the ratio of the carbon fluoride material, the nanocarbon material and the interface stabilizer in the interface stabilization layer, etc., to further stabilize the structure of the composite negative electrode and improve the electrochemical performance;
[0040] (5) The preparation method provided in this application has a short process flow, high production efficiency and universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a physical photo of the composite negative electrode in Example 2;
[0042] Figure 2 It is the cycle test curve of Example 2 and Example 4;
[0043] Figure 3 1 is the cycle test curve of Example 2 and Example 10;
[0044] Figure 4 These are the cycle test curves of Example 2, Comparative Example 1, Comparative Example 3 and Comparative Example 5. DETAILED DESCRIPTION
[0045] To facilitate understanding of the present application, the present application lists the following embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.
[0046] Example 1
[0047] This embodiment provides a composite negative electrode, which includes a 100 μm metal lithium strip and a 1 μm interface stabilization layer, wherein the interface stabilization layer includes fluorinated carbon black, multi-walled carbon nanotubes and styrene-butadiene rubber.
[0048] The method for preparing the composite negative electrode comprises the following steps:
[0049] (1) 0.1 g of multi-walled carbon nanotubes (XFM67, length 10-20 μm, outer diameter 4-6 nm, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), 1 g of fluorinated carbon black (Shanghai Furui Fine Chemical Co., Ltd., fluorine-carbon ratio 1.0, particle size 50-100 nm) and 0.01 g of styrene-butadiene rubber (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were mixed in n-hexane and mixed at a rotation speed of 6000 rpm for 6 h to obtain a mixture;
[0050] (2) In a clean room with a dew point of -60°C, the mixture is placed on the surface of a metal lithium strip by screen printing, and the n-hexane is removed at 100°C to obtain the composite negative electrode.
[0051] Example 2
[0052] This embodiment provides a composite negative electrode, which includes a 100 μm lithium-tin (the mass fraction of tin is 20%) alloy strip and a 2 μm interface stabilization layer, wherein the interface stabilization layer includes fluorinated graphene, single-walled carbon nanotubes and styrene-ethylene-butylene-styrene block copolymer.
[0053] The method for preparing the composite negative electrode comprises the following steps:
[0054] (1) 1 g of single-walled carbon nanotubes (Okoshiel Trading (Shenzhen) Co., Ltd., diameter 1 nm, length 5 μm, 3 wt%), 0.1 g of fluorinated graphene (Shandong Chongshan Optoelectronic Materials Co., Ltd., fluorine-carbon ratio 1.2, sheet diameter 8-10 μm) and 10 g of styrene-ethylene-butylene-styrene block copolymer (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were mixed in solvent oil D40 and mixed at a rotation speed of 8000 rpm for 10 h to obtain a mixture;
[0055] (2) In a clean room with a dew point of -60°C, the mixture is coated on a PET release film, the solvent oil D40 is removed at 80°C, and then the mixture is rolled onto the surface of a lithium-tin alloy strip by transfer to obtain the composite negative electrode. Figure 1 shown. Figure 1 The interfacial stabilization layer and the lithium-tin alloy ribbon adjacent to the interfacial stabilization layer are shown in FIG.
[0056] Example 3
[0057] This embodiment provides a composite negative electrode, which includes a lithium-copper composite tape (1 μm of metallic lithium is evaporated on the surface of the copper foil) and a 10 μm interface stabilization layer, wherein the interface stabilization layer includes fluorinated carbon nanotubes, Ketjen black and styrene-ethylene-styrene block copolymer.
[0058] The method for preparing the composite negative electrode comprises the following steps:
[0059] (1) 0.5 g of graphene (sheet diameter: 0.5-5 μm, thickness: 0.8-1.2 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), 1 g of graphite fluoride (purchased from Shanghai Furui Fine Chemical Co., Ltd., average particle size 5-10 μm, fluorine-carbon ratio: 1.15) and 0.25 g of styrene-ethylene-styrene block copolymer (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were mixed in p-xylene and mixed at a rotation speed of 1000 rpm for 8 h to obtain a mixture;
[0060] (2) In a clean room with a dew point of -60°C, the mixture is directly coated on a lithium-copper composite tape, and p-xylene is removed at 100°C to obtain the composite negative electrode.
[0061] Example 4
[0062] Compared with Example 2, the only difference is that the thickness of the lithium-tin alloy strip is replaced with 2 μm. At this time, the thickness ratio of the interface stabilization layer to the lithium-tin alloy is 1:1, and the other conditions are the same.
[0063] Example 5
[0064] Compared with Example 2, the only difference is that the thickness of the interface stabilization layer is replaced with 5 μm. At this time, the thickness ratio of the interface stabilization layer to the lithium-tin alloy is 1:20, and the other conditions are the same.
[0065] Example 6
[0066] Compared with Example 2, the only difference is that the thickness of the interface stabilization layer is replaced with 20 μm. At this time, the thickness ratio of the interface stabilization layer to the lithium-tin alloy is 1:5, and the other conditions are the same.
[0067] Example 7
[0068] Compared with Example 2, the only difference is that the thickness of the interface stabilization layer is replaced with 10 μm. At this time, the thickness ratio of the interface stabilization layer to the lithium-tin alloy is 1:10, and the other conditions are the same.
[0069] Example 8
[0070] Compared with Example 2, the only difference is that the lithium-tin alloy strip is replaced by a lithium-boron-indium alloy strip (the mass fraction of boron is 1%, and the mass fraction of indium is 9%).
[0071] Example 9
[0072] Compared with Example 2, the only difference is that the lithium-tin alloy strip is replaced by lithium-tin-magnesium alloy strip particles (the mass fraction of tin is 8%, and the mass fraction of magnesium is 2%).
[0073] Example 10
[0074] Compared with Example 2, the only difference is that the masses of single-walled carbon nanotubes and styrene-ethylene-butylene-styrene block copolymer are replaced with 0.5g and 0.25g respectively. At this time, the mass ratio of single-walled carbon nanotubes, fluorinated graphene and styrene-ethylene-butylene-styrene block copolymer is 5:1:2.5.
[0075] Embodiment 11
[0076] Compared with Example 2, the only difference is that the interface stabilization layer is embedded in the lithium-tin alloy strip with an embedding thickness of 0.5 μm and the embedding method is rolling.
[0077] Comparative Example 1
[0078] Compared with Example 2, the only difference is that the interface stabilizing layer is replaced by fluorinated carbon material and styrene-ethylene-butylene-styrene block copolymer, and the other conditions are the same as those in Example 2.
[0079] Comparative Example 2
[0080] Compared with Example 2, the only difference is that the interface stabilizing layer is replaced by single-walled carbon nanotubes and styrene-ethylene-butylene-styrene block copolymer, and the other conditions are the same as those in Example 2.
[0081] Comparative Example 3
[0082] Compared with Example 2, the only difference is that the interface stabilizing layer contains only single-walled carbon nanotubes, and does not contain fluorinated graphene and styrene-ethylene-butylene-styrene block copolymer.
[0083] Comparative Example 4
[0084] Compared with Example 2, the only difference is that the interface stabilizing layer contains only fluorinated graphene but does not contain single-walled carbon nanotubes and styrene-ethylene-butylene-styrene block copolymer.
[0085] Comparative Example 5
[0086] Compared with Example 2, the only difference is that the single-walled carbon nanotubes and fluorinated graphene are replaced by Ketjen black (purchased from Dongguan Kelude New Energy Technology Co., Ltd., EC-600JD) and fluorinated graphite, respectively, both of which are granular materials.
[0087] Comparative Example 6
[0088] Compared with Example 2, the only difference is that the interface stabilizing layer adopts the protective layer disclosed in Example 3 in CN110957492A.
[0089] Comparative Example 7
[0090] Compared with Example 2, the only difference is that no interface stabilization layer is provided, and only a lithium-tin alloy strip is provided.
[0091] Comparative Example 8
[0092] Compared with Example 2, the only difference is that the styrene-ethylene-butylene-styrene block copolymer is replaced by polyvinylidene fluoride, and the other conditions are the same.
[0093] Comparative Example 9
[0094] Compared with Example 2, the only difference is that the styrene-ethylene-butylene-styrene block copolymer is replaced by polyethylene oxide, and the other conditions are the same.
[0095] Test data:
[0096] The negative electrode in Example 1-11 and Comparative Example 1-9 was assembled with the NCM811 positive electrode to test the soft pack battery. The electrolyte was an ether electrolyte (purchased from Shenzhen Kejing Zhida Technology Co., Ltd.). The cycle performance was tested at 25°C and 0.5C / 1C charge and discharge conditions. The test was stopped when the discharge capacity reached 80% of the first cycle discharge capacity or short circuit or overcharge occurred. The cycle data are shown in Table 1.
[0097] Table 1 Test data of negative electrode
[0098]
[0099] From Table 1, we can see that:
[0100] (1) Combining Example 2 and Example 4-7, it can be seen that the cycle performance of the soft-pack battery of Example 4-7 is better than that of Example 2. This is because the thickness ratio of the interface stabilizing layer and the lithium-containing layer in Example 4-7 is within the preferred range of the present application, which is more appropriate. The two cooperate with each other, so that the composite negative electrode has a stable structure and good interface stability, and has both rate performance and cycle performance; combined with Figure 2 It can be seen that the cycle stability of the composite negative electrode of Example 4 is better than that of Example 2;
[0101] (2) Combining Example 2 and Examples 8-9, it can be seen that the cycle performance of Example 8-9 is better than that of Example 2. This is because the lithium-containing layer used in Examples 8-9 is a ternary alloy, and the alloy elements cooperate with each other to regulate the uniform deposition of metallic lithium, thereby significantly improving the cycle performance and rate performance of the composite negative electrode;
[0102] (3) Combining Example 2 and Example 10, it can be seen that the cycle performance of Example 10 is better than that of Example 2. This is because the content ratio of each component in the interface stabilization layer in Example 10 is within the preferred range of the present application, which is more appropriate. The components cooperate with each other to construct a more stable interface stabilization layer, which effectively improves the performance of the composite negative electrode. Figure 3 It can be seen that the cycle stability of the composite negative electrode of Example 10 is better than that of Example 2;
[0103] (4) Combining Example 2 and Example 11, it can be seen that the cycle performance of Example 11 is better than that of Example 2. This is because the lithium-containing functional layer in the composite negative electrode of Example 11 is embedded in the lithium-containing layer, making the composite negative electrode structure more stable;
[0104] (5) Combining Example 2 and Comparative Examples 1-4, it can be seen that the cycle performance of Example 2 is better than that of Comparative Examples 1-4. This is because the selection of the components of the interface stabilization layer in Example 2 is better than that in Comparative Examples 1-4. Specifically, the components of the interface stabilization layer in Example 2 work synergistically (can be cycled 213 times), Comparative Example 1 can be cycled 109 times, and Comparative Example 3 can be cycled 87 times. The number of cycles of both or the sum of the number of cycles is lower than that of Example 2; similarly, Comparative Example 2 can be cycled 95 times and Comparative Example 4 can be cycled 98 times. The number of cycles of both or the sum of the number of cycles is lower than that of Example 2. Therefore, the components of the interface stabilization layer in Comparative Examples 1-4 are different from those in Example 2, and they cannot achieve the effect of the interface stabilization layer in the present application; combined Figure 4 It can be seen that the cycle stability of Comparative Examples 1 and 3 is worse than that of Example 2, and the capacity decay during the cycle process is relatively rapid;
[0105] (6) Based on Example 2 and Comparative Example 5, it can be seen that the cycle performance of Example 2 is better than that of Comparative Example 5. This is because the interface stabilization layer in Comparative Example 5 uses granular nanocarbon materials and fluorinated carbon materials. When forming the interface stabilization layer, it is point contact and cannot form an effective connection. In addition, the components are connected closely to the interface stabilizer, and the connection effect is worse than that of Example 2. The single-walled carbon nanotubes and fluorinated graphene in Example 2 are non-granular materials, which can play the role of connecting the components. Figure 4 It can be seen that the cycle stability of Comparative Example 5 is worse than that of Example 2, and the capacity decays rapidly during the cycle process;
[0106] (7) Based on Example 2 and Comparative Example 6, it can be seen that the cycle performance of Example 2 is better than that of Comparative Example 6. This is because there is no interface stabilizer in Comparative Example 6, and the structure of the protective layer is unstable and easy to fall off or break;
[0107] (8) Based on Example 2 and Comparative Example 7, it can be seen that the cycle performance of Example 2 is better than that of Comparative Example 7. This is because Comparative Example 7 does not contain an interfacial stabilizing layer, and the side reaction between the lithium-containing layer and the electrolyte is relatively large;
[0108] (9) Based on Example 2 and Comparative Examples 8-9, it can be seen that the cycle performance of the soft-pack battery in Example 2 is better than that in Comparative Example 8. This is because the interface stabilizer styrene-ethylene-butylene-styrene block copolymer in Example 2 includes hard and strong styrene structural units and soft and elastic olefin units, forming a network structure, so that the interface stabilization layer has elasticity and can adapt to the volume change of the lithium-containing layer during the cycle. However, the polyvinylidene fluoride and polyethylene oxide in Comparative Examples 8-9 do not have hard and strong styrene structural units and do not have the characteristics of enhancing interface mechanics. As the cycle progresses, the effect is not as good as that of styrene-ethylene-butylene-styrene block copolymer.
[0109] The applicant declares that the present application illustrates the detailed structural features of the present application through the above-mentioned embodiments, but the present application is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present application must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement to the present application, equivalent replacement of the components selected by the present application, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present application.
Claims
1. A metal lithium composite negative electrode, characterized in that: The composite negative electrode comprises a lithium-containing layer, and an interface stabilization layer is arranged on the surface of the lithium-containing layer; the interface stabilization layer comprises a micro-nano carbon fluoride material, a nano-carbon material and an interface stabilizer, and lithium fluoride is generated in situ at the contact position between the carbon fluoride material and the lithium-containing layer; At least one of the fluorinated carbon material and the nano-carbon material is a linear, tubular or sheet-shaped material, the interfacial stabilizer includes a styrene structural unit, The fluorinated carbon material includes at least one of fluorinated graphite, fluorinated activated carbon, fluorinated carbon black, fluorinated carbon nanotubes, fluorinated nanocarbon fibers, fluorinated graphene or fluorinated graphene oxide; the nanocarbon material includes at least one of carbon nanofibers, carbon nanotubes, graphene, acetylene black, Super P carbon black or Ketjen black.
2. The composite negative electrode according to claim 1, characterized in that The lithium-containing layer includes metallic lithium and / or a lithium alloy, wherein the alloying elements in the lithium alloy include at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum or zinc, and the content of metallic lithium in the lithium alloy is greater than 50%; The thickness of the lithium-containing layer is 1-100 μm.
3. The composite negative electrode according to claim 1, characterized in that: The atomic ratio of carbon to fluorine in the fluorinated carbon material is greater than 0 and less than 1.25; The size of the fluorinated carbon material is 1 nm-50 μm.
4. The composite negative electrode according to claim 1, characterized in that: The number of layers of the carbon nanotubes and graphene is independently less than or equal to 15 layers; The outer diameter of the carbon nanotube is less than 30 nm; The length of the carbon nanotubes is 0.5 μm to 100 μm; The sheet diameter of the graphene is 1-20 μm.
5. The composite negative electrode according to claim 1, characterized in that: The interfacial stabilizer comprises a copolymer of styrene and olefin, wherein the copolymer of styrene and olefin is at least one of styrene-butadiene rubber, polystyrene, styrene-ethylene-styrene block copolymer, styrene-propylene-styrene block copolymer, styrene-butadiene-styrene triblock copolymer or styrene-ethylene-butylene-styrene block copolymer; The mass ratio of the fluorinated carbon material to the nano-carbon material in the interface stabilization layer is 1:(0.1-10); The mass ratio of the nano-carbon material to the interface stabilizer in the interface stabilization layer is 1:(0.1-10); The mass ratio of the fluorinated carbon material, the nanocarbon material and the interface stabilizer in the interface stabilization layer is (0.1-10):1:(0.1-10); The thickness of the interfacial stabilization layer is 1-20 μm; The thickness ratio of the interface stabilizing layer to the lithium-containing layer is 1:(0.1-100).
6. The composite negative electrode according to claim 1, characterized in that: The interface stabilizing layer is embedded in the lithium-containing layer, and the embedding depth is 0.1-5 μm.
7. The composite negative electrode according to any one of claims 1 to 6, characterized in that: The composite negative electrode further includes a current collector, which includes at least one of copper foil, carbon-coated copper foil, textured copper foil, nickel foil, stainless steel foil, copper-tin composite foil or copper-nickel composite foil.
8. A method for preparing the composite negative electrode according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) mixing a fluorinated carbon material, a nanocarbon material, an interface stabilizer and an organic solvent to obtain a mixture; (2) placing the mixture in step (1) on the surface of the lithium-containing layer to obtain the composite negative electrode, The organic solvent in step (1) includes at least one of liquid alkanes with a carbon number of 5 to 20, benzene, p-xylene, solvent oil D40, solvent oil D60, solvent oil D80, N-methylpyrrolidone or N,N-dimethylformamide.
9. The method according to claim 8, characterized in that Step (2) also includes the following operation: placing the mixture on the surface of the lithium-containing layer and then rolling it.
10. A metal lithium battery, characterized in that: The metal lithium battery comprises the composite negative electrode as described in any one of claims 1 to 7.
Citation Information
Patent Citations
A surface modification method for lithium anode in lithium metal batteries and lithium metal batteries
CN108448058B
Lithium metal interface protection, preparation method thereof and battery containing lithium metal interface protection
CN110957492A
Preparation method and application of metal lithium battery with sandwich structure and long life
CN109686922A
Interface protection structure, preparation method and battery comprising structure
CN109728249A
Preparation method of negative pole piece, negative pole piece and lithium battery
CN116190577A